PEMBELAJARAN ANAK USIA DINI DI MASA PANDEMI COVID-19 - Harwanti Noviandari; Evi Febriani (Program Studi pendidikan Islam Anak Usia Dini, Fakultas Tarbiyah Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2020)
This study aims to describe the role of parents in assisting early childhood learning in the corona virus pandemic at home. The research method uses qualitative descriptive approach. The study subjects numbered five families who have preschool-aged children. Determination of the subject using a purposive sampling technique that is the criteria of families who have pre-school age children that are aged 3-6 years and located Kebalenan Indah Housing Kebalenan Village Data collection is done by interview, observation, and documentation. Data analysis using the Miles and Huberman model with the stages of data collection, data reduction, data display, and data fermentation. The conclusion of this study is that parents have difficulty carrying out their role in assisting children's learning during the Covid-19 pandemic so that children's tendencies are left to play alone because parents have some constraints examples of children sometimes tend to ignore when parents provide learning at home on the other hand have tricks to provide a learning process for children even though assistance, explanation, as well as persuasion and persuasion especially for children is also difficult for children to follow. However, the learning process must be given even in the days of the Covid-19 pandemic. assistance is done more by mothers than fathers. So that collaboration and the role of fathers are needed to support and complete the efforts made by mothers in learning at home during the Covid-19 pandemic to children.